Дослідження роботи двох свердловин - Василенков, В. Є.; Гайдук, О. І. (Енергетика і автоматика, 2017)
UDC 631.3RESEARCH WORK TWO Water TowerV. Vasilenkov, A. Hayduk For agricultural water supply scheme is typical of underground sources consisting of wells with pumps, pressure water supply, water tower and water consumers with multiple ramifications. The volume of the water tower depends on the maximum daily consumption of water treatment works pumping station. The main disadvantage of this major water schemes is that in the event of failure of one working well water tower is unable to provide normal functioning of the consumers.Objective: To improve the reliability of water supply customers in the period of force majeur.Materials and methods of research. To achieve this goal proposed a water system consisting of working wells with pumps, pressure water supply, water tower and water consumers with multiple ramifications to existing wells to establish an additional one backup well, which should provide water consumers during the failure of labor well.Results. The electrical schematic diagram of the control wells consists of two boards submersible pump, which manages the two pumps and two wells switching circuits depending on the disability.The first set of equipment performs the basic function - enables or disables the motor pump the first or second hole, depending on the water level in the water tower. It consists of a sensor lower level and upper level sensor, which are installed in the water tower. Secondary device on the shield the motor starts and stops pumping unit circle 3 or 4 and signaled their work. The composition of this kit also includes a software unit through which the electric pump-on delay of the second hole. This provided complete switching of dvohahrehatnoyi pumping unit.The second set of sensors protects from failure in the event of icing in winter. It consists of a hand control unit (second) switching on the heating element.The third and fourth sets show the pressure in the water system consists of showing a device that is installed in place.ConclusionsWater supply from underground sources, using 2 wells will: increase the reliability of water supply almost 100 %; reduce koroziynist pipes with no water; raise the level of services provided by housing and utilities.